Nannobiostratigraphy of The Mushorah Formation in (AZ.29) well, Ain Zalah oil field, Northwestern Iraq - Al-Hadeedy, Mahfoudh Abdulla; Al-Badrani, Omar Ahmed; Hassan, Faris Nejris (Sulaimani Journal for Pure and Applied Sciences, 2023)
A Detailed calcareous nannofossils study for the Mushorah Formation from subsurface section at Az. (29) well, Ain Zalah oil field, Northwestern Iraq. This is the first documentation of calcareous nannofossils in the Mushorah Formation, the Paleontological classification of this flora led to determine forty species. The nannobiostratigraphic analysis suggested three calcareous nannofossils biozones these are: (1) Calculites obscurus Interval Biozone; (2) Broinsonia parca Interval Biozone; (3) Misceomarginatus pleniporus Interval Biozone. These biozones concluded that the age of studied section of the Mushorah Formation is Early to Middle Campanian
Keywords: Campanian; the Mushorah Formation; Calcareous Nannofossils; Iraq